PENGARUH VARIASI ARUS DAN WAKTU PENEKANAN PADA PROSES SPOT WELDING TERHADAP KEKUATAN TARIK SAMBUNGAN GRILL DIFFUSER BERBAHAN BAJA KARBON RENDAH: Pengaruh Variasi Arus Dan Waktu Penekanan Pada Proses Spot Welding Terhadap Kekuatan Tarik Sambungan Grill Diffuser Berbahan Baja Karbon Rendah Title The Effect of Current Variation and Holding Time in the Spot Welding Process on the Tensile Strength of Low Carbon Steel Grill Diffuser Joints - Bambang Triono; Nur Irfan Islail (Jurnal Pendidikan Teknik Mesin Undiksha, 2024)
This study aims to analyze the effect of variations in welding current and electrode holding time in the spot welding process on the tensile strength of joints in low carbon steel grill diffuser components. Spot welding is widely used in the manufacturing industry, particularly for joining low carbon steel materials, where joint quality is highly influenced by process parameters such as welding current and holding time.This research employed an experimental method, with welding current and holding time as independent variables, and tensile strength of the welded joint as the dependent variable. The welding current variations used in this study were 80 kA and 90 kA. Tensile testing was conducted to determine the maximum strength of the welded joints.The results indicate that increasing the welding current tends to improve the tensile strength of the joint up to an optimum level; however, excessive current may lead to welding defects such as expulsion, which reduces joint strength. Meanwhile, longer holding time contributes to better bonding quality through improved nugget formation. The optimal combination of welding current and holding time produces the highest tensile strength in the welded joints.Therefore, proper control of spot welding process parameters is essential to enhance the quality and mechanical strength of grill diffuser joints made of low carbon steel.